2020
DOI: 10.1029/2020jc016368
|View full text |Cite
|
Sign up to set email alerts
|

Annual and Seasonal Surface Circulation Over the Mid‐Atlantic Bight Continental Shelf Derived From a Decade of High Frequency Radar Observations

Abstract: A decade (2007-2016) of hourly 6-km-resolution maps of the surface currents across the Mid-Atlantic Bight (MAB) generated by a regional-scale High Frequency Radar network are used to reveal new insights into the spatial patterns of the annual and seasonal mean surface flows. Across the 10-year time series, temporal means and interannual and intra-annual variability are used to quantify the variability of spatial surface current patterns. The 10-year annual mean surface flows are weaker and mostly cross-shelf n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In the same way as for drifter data, the aim is to process these velocities to obtain synthetic velocities with the physical content of geostrophic MDT velocities. We used the cleaned, detited, high-frequency signal-filtered and mean currents over the period 2006-2016, processed by Rutgers University (Roarty et al 2020). Then the mean wind-driven currents over the same period (U Ekman taken from the Copernicus-Globcurrent product MULTIOBS GLO PHY REP 015 004) were removed and finally these mean currents were re-referenced to the 1993-2012 reference period.…”
Section: Computation Of the Synthetic Mean Velocitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way as for drifter data, the aim is to process these velocities to obtain synthetic velocities with the physical content of geostrophic MDT velocities. We used the cleaned, detited, high-frequency signal-filtered and mean currents over the period 2006-2016, processed by Rutgers University (Roarty et al 2020). Then the mean wind-driven currents over the same period (U Ekman taken from the Copernicus-Globcurrent product MULTIOBS GLO PHY REP 015 004) were removed and finally these mean currents were re-referenced to the 1993-2012 reference period.…”
Section: Computation Of the Synthetic Mean Velocitiesmentioning
confidence: 99%
“…This new CNES-CLS22 MDT also uses velocity data estimated from HF radars located in the Mid Atlantic Bight area, East coast of the US from Cape Hatteras to Cape Cod. We used the cleaned, detited, high-frequency signal-filtered and mean currents over the period 2006-2016 (processed by Rutgers University, Roarty et al 2020).…”
Section: Datamentioning
confidence: 99%
“…For example, land-sourced microbial communities which are transported in air (Mayol et al, 2017) or water runoff (Adyasari et al, 2020) change the microbial communities found in coastal ocean waters, and this could have a protracted effect in summer when water circulates more slowly. During the summer, the Gulf Stream slows along eastern North America as warming land temperatures alter winds and push them across coastal water currents on an east-west axis, rather than with water currents on a northward path (Roarty et al, 2020). Around Cape Cod, summer winds contribute to a recirculating eddy in Massachusetts Bay which does not mix with deeper water nearly as much as it does in winter (Robinson, 2005).…”
Section: Warmer Water Could Alter How and Which Microorganisms Are Ca...mentioning
confidence: 99%
“…In addition, several studies have investigated the small-to medium-scale near-shore processes, such as the cross-shore transport of surface water and the transport of surface biological communities and chemicals [22][23][24], since their transports are of environmental and ecological importance. Meanwhile, the long-term characteristics of the HFR-derived current have also been investigated, such as the characteristics of surface circulation on the west and east coasts of the United States revealed by Kim and Roarty, respectively [25,26]. In Australia, the seasonal and multi-year characteristics of the East Australian Current (EAC) have also been studied by Mao [14] and Archer [11].…”
Section: Introductionmentioning
confidence: 99%